Palaeontological Society of Southern Africa - 15th Biennial Meeting, Grahamstown, 2006 - Additional Abstracts - Various (Bernard Price Institute for Palaeontological Research, University of the Witwatersrand, 2008)
The following three abstract were inadvertently omitted from the list of abstracts published in Palaeontologia africana (2007) 42, 117–136.
Keywords: Palaeontological Society of Southern Africa; Abstracts